1985
DOI: 10.1111/1523-1747.ep12264711
|View full text |Cite
|
Sign up to set email alerts
|

The Permeability of Skin and Oral Mucosa to Water and Horseradish Peroxidase as Related to the Thickness of the Permeability Barrier

Abstract: The permeability of porcine skin and keratinized and nonkeratinized oral mucosa to tritium-labeled water and horseradish peroxidase (HRPO) was determined using perfusion chambers. Small blocks from each tissue were also incubated with HRPO and the extent of penetration visualized microscopically; this enabled measurements to be made of the thickness of the permeability barrier to this water-soluble tracer. Results obtained after inverting the oral mucosa in the chambers or adding metabolic inhibitors indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(53 citation statements)
references
References 15 publications
4
48
0
1
Order By: Relevance
“…These workers reported that this 20% of the oral mucosa accounted for between 75 and 80% of oral carcinomas, and Mashberg (1980) also found that 66% of oral carcinomas originate in the floor of the mouth or on the ventral surface of the tongue. These regions also appear to be the most permeable to tritiated water in both the pig (Squier and Hall, 1985) and the human (Lesch et al, 1987), and their possible higher permeability to other substances, such as carcinogens, has been postulated as a factor in their particular susceptibility to development of carcinoma (Lesch et at., 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These workers reported that this 20% of the oral mucosa accounted for between 75 and 80% of oral carcinomas, and Mashberg (1980) also found that 66% of oral carcinomas originate in the floor of the mouth or on the ventral surface of the tongue. These regions also appear to be the most permeable to tritiated water in both the pig (Squier and Hall, 1985) and the human (Lesch et al, 1987), and their possible higher permeability to other substances, such as carcinogens, has been postulated as a factor in their particular susceptibility to development of carcinoma (Lesch et at., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on porcine oral mucosa, Squier and Hall (1985) found that the floor of the mouth was significantly more permeable than any other site in the oral cavity, while the keratinized gingival epithelium was closer in water permeability to epidermis. Studies on the permeability of oral mucosa from cadavers, by Lesch et al (1987), also showed that the floor of the mouth and lateral borders of the tongue were the most permeable regions.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these aspects, acceptability to the patient, drug release profile, and the practicality of using them also play an important role. [4][5][6] Type of mucosa, thickness of mucosa and keratinization: The permeability drug across the mucosa may vary depending on the thickness of the oral mucosa at different sites. Keratinized mucosa is less permeable to the drugs as compared to the non-keratizied mucosa.…”
Section: Mechanism Of Topical Drug Delivery and Characteristic Of Oramentioning
confidence: 99%
“…The difficulty in using rabbit oral mucosa, however, is the sudden transition to keratinized tissue at the mucosal margins making it hard to isolate the desired non-keratinized region 53 . The oral mucosa of larger experimental animals that has been used for permeability and drug delivery studies include monkeys 54 , dogs 35,40,55,56 and pigs 57,58,[59][60][61][62][63] .…”
Section: Experimental Animal Speciesmentioning
confidence: 99%